THE USE OF DEBATE TECHNIQUE TO IMPROVE STUDENTS’ SPEAKING ABILITY - Liu, Yang Yang; Rufinus, Albert; Susilawati, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was done to investigate how debate technique can improve students’ speaking ability. The form of this research is a classroom action research, in which the subject is the eleventh grade students of SMAN 10 Pontianak in academic year 2017/2018. The subjects of this research were 36 students in XI IPA 3. The data were collected from the students’ score in speaking test, observation checklist, video recording and field notes. The students’ attitude towards the learning process was gathered by observation checklist and field note. The data of speaking was obtained by speaking test which was administered through debate technique. Based on data, the students showed improvement in the process of debate technique. There were two cycles in conducting this research. In cycle I, the students could explore the rules and language features of debate technique, but less in organizing the time. The researcher conducted the cycle II which resulted that, the students could deliver the arguments and comprehend the debate technique. Besides that, the teacher was able to engage students’ performance in speaking spoken form of analytical exposition text by the use debate technique and the students also became more active and enthusiastic in teaching learning process.Key words: Debate Technique, Improve, Speaking Ability